Perception of influences on the diet of elderly people from the Lan-C sector of Hualpén commune, Chile - Troncoso Pantoja, Claudia (2017)
Objective: To interpret the perception of influences on the diet of elderly people from the Lan-C sector of Hualpén commune, Chile, during the year 2016. Materials and methods: In order to accomplish the objective, researchers used a qualitative design with an interpretative phenomenological approach. The qualitative sampling was performed by the snowball method. The sample size was not determined a priori, but through theoretical saturation; that is, when interviews did not provide new data to the research, which happened in the fifth interview. Subjects included in the study fulfilled the screening criteria, such as being over 60 years old, not having cognitive damage that prevented a fluent conversation, not being diagnosed with any form of dementia, living in the Lan-C sector of Hualpén commune, and signing an informed consent of the research with which ethical aspects of the study were controlled. Data collection was performed through semi-structured interviews. The results were coded and analyzed through the content analysis method. Results: Interviewees mentioned that their diet was influenced by their family, emotions and economic situation. The family, especially their children, had a positive influence on their diet by selecting the food they were to consume, preparing their meals, and maintaining or improving their health through the diet. They also stated that the economic situation affected their diet and, although they had a limited income, they favored the purchase of healthy food which would allow them to keep an adequate quality of life. Regarding their emotions, they especially refer to memories of their childhood and youth, their mother and special dates which have influence on their diet. Other factors, such as advertisement or friends, were not identified as conditioning their eating behavior. Conclusion: There are some factors that affect the diet of elderly people, such as their emotions, economic situation and family.